JURIDICAL REVIEW OF THE TRANSFER OF LAND OWNERSHIP RIGHTS THAT ARE TRADED BY PLOT IN SUMBAWA REGENCY - Elma Apriani; Hilman Syahrial Haq; M. Taufik Rachman (Universitas Muhammadiyah Mataram, 2024)
The research entitled